Communes and workers' control in Venezuela : building 21st century socialism from below - Azzellini, Dario, 1967- (Historical materialism book series, 2017)
In Communes and Workers' Control in Venezuela: Building 21st Century Socialism from Below , Dario Azzellini offers an account of the Bolivarian Revolution from below. While authors on Venezuela commonly concentrate on former president Hugo Chávez and government politics, this book shows how workers, peasants and the poor in urban communities engage in building 21st century socialism through popular movements, communal councils, communes and fighting for workers' control. In a relationship of cooperation and conflict with the state, social transformation is approached on 'two tracks', from below and from above. Azzellini's fascinating account stands out because of the extensive empirical examples and original voices from movements, communal councils, communes and workers.